Cohesion in journal articles on applied linguistics: the case of conjunction “thus” - Arina Isti'anah; Stephanie Permata Putri; Anggita Getza Permata (Politeknik Negeri Bali, 2020)
Cohesion plays an important role in building the readability and comprehension of a text. Instead of lexical, reference, substitution, and reference, the conjunction is also important in a text. One of which is “thus” which shows how the message is packaged in the text. Journal articles become the major source for scholars to share and connect their ideas. The ‘standard’ writing including content and format is one of the concerns in the article publication. The employment of conjunction in the article is important to show the author’s logical connection between her or his ideas. By employing discourse analysis by Halliday and Hassan, this paper aims at finding out the cohesion of journal articles of applied linguistics seen from the employment of conjunction “thus” adopting Martin and Rose’s theory on a logical connection. Purposive sampling method was conducted by taking forty journal articles on applied linguistics. AntConc, a corpus web, was employed to help the researches figure out how conjunction “thus” is used in the text in building the cohesion of the data.